Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Socially responsible medical education: innovations and challenges in a minority setting - Schofield, Aurel; Bourgeois, Daniel (Medical Education, 2010)
Context Distributed medical education sites help train, recruit and retain doctors, notably in rural and isolated areas, by providing education and training in these areas and adapting their curriculum to meet the host community’s health needs. Objectives The Centre de Formation Médicale du Nouveau Brunswick (CFMNB; New Brunswick Medical Education Centre) was established by a partnership between two academic institutions, the Université de Sherbrooke (University of Sherbrooke), situated in the province of Quebec, and the Université de Moncton (University of Moncton), situated in the province of New Brunswick, in Canada. The CFMNB is specifically targeting a minority community (Acadians). Working to establish a high‐quality medical education programme, the CFMNB has also set community objectives to meet not only the health needs of this population, but also its social and economic needs. Methods This paper describes the overall objectives of this project, which are: to reduce the gap between community needs and academic institutional needs; to address ethno‐cultural and language differences in a defined minority population, and to develop collaboration between the partners involved, including government and community entities which are often perceived as operating in isolation from one another. We also describe why and how the CFMNB developed community‐focused objectives and the challenges that came with these innovations, and present lessons from the experience that may be relevant to other sites interested in the social responsibility of medical schools. Conclusions The CFMNB has produced interesting work and innovations in the field of social responsibility and has encountered many challenges. Continuing interaction between medical education, health research and health services to better address the needs of the population has been established. The information obtained by this process has been used to build a strategic plan for the CFMNB in order to ensure that it is socially responsive and has significant generalisable features.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.